Estudo de parâmetros da ventilação natural para maximização do conforto térmico em pavilhões industriais - Oliveira, Enaira Hoffmann de (2012)
The concerning with the increase of energy consumption for the building thermal conditioning and the occupant wellbeing encourages the evaluation of buildings regarding their environmental performance. The natural ventilation optimization in factories can contribute to the decreasing of energy consumption by the use of air conditioners, resulting in environmental benefits like electric energy reduction and the thermal comfort increasing. Thereby, the natural ventilation is one of the strategies of natural conditioning offering thermal comfort to an industrial environment. Despite its importance, the construction guidelines that involve the building thermal improvement are mostly determined empirically, do not comprehending all the short of factors of a project. This work proposes the applying of these optimization techniques using the environmental comfort parameters in industrial environments. The aim is to maximize the thermal comfort in pavilions, with or without wind effects, using as variables the dimensions and the openings positions, reducing the energy consumption based on the chosen methodology for subsequent projects. From the simulations using a set of opening and pavilion sizes and configurations, the relation between opening áreas and the pavilion volumes, the relation between the opening áreas and the pavilion floor áreas and the relation between enter and exit opening áreas were pointed out as parameters for the project. These optimized relations were compared with data available in technical literature. Among others, simulation results indicate a huge reduction in opening áreas needed, when Wind plays a major role, if compared with the cases in which there are just the chimney effect